A Comprehensive Survey of Dynamic Data Mining Process in Knowledge Discovery Database - Kumar, D. Ramana; Rao, S. Krishna Mohan; Rao, K. Rajeshwar (International Journal of Computer Sciences and Engineering, 2018)
Data mining and knowledge discovery in databases have been considered as a significant research area in industry. This survey presents an overview, description and future directions which depict a standard for knowledge discovery and data mining process model. The paper mentions particular real-world applications, specific data mining techniques, challenges involved in real-world application of knowledge discovery, current and future research ideas in the field. The applications to both academic and industrial problems are discussed. The main target of the review is the consolidation of the research in this particular area and thereby helping in enhancing the existing model by embedding other current standards.